Community-based conservation of freshwater resources: Learning from a critical review of the literature and case studies - Zhang, Wei; ElDidi, Hagar; Masuda, Yuta J.; Meinzen-Dick, Ruth S.; Swallow, Kimberly A.; Ringler, Claudia; DeMello, Nicole; Aldous, Allison (Informa UK Limited, 2023)
Freshwater resources (FWRs) are under enormous stress due to human activities and climate change. Given the centrality of local communities in managing natural resources, community-based conservation (CBC) for FWRs (fCBC) offers a mechanism for addressing these challenges. A framework informing fCBC that incorporates unique features of FWRs (such as being fugitive resources, having increased risk of negative externalities, and sheer spatial coverage) is needed to unlock CBC’s potential in achieving environmental and developmental impacts in freshwater contexts. We critically review and synthesize existing research adapting The Nature Conservancy’s Voice, Choice and Action framework, organized around four pillars (Secure rights and fair externality consideration; Strong community capacity; Effective multi-stakeholder platforms; Sustainable livelihood and development opportunities) and two cross-cutting elements (Cultural connections; Equity and power balancing), and provide recommendations on ways to strengthen facilitation and support community empowerment in fCBC. We report on how applying the framework during a conservation planning process for fCBC projects in four geographies provides important insights for developing robust CBC programs.